Sosialisasi dan Pendampingan Skrining Riwayat Kesehatan Mandiri pada Pasien BPJS Kesehatan di Puskesmas Sedati - Amalia, Nuke; Rustam, Muh Zul Azhri; Amalin, Atika Mima; Susanti, Ari; Riestiyowati, Maya Ayu; Suhardiningsih, A.V. Sri (STIKES Yayasan RS.Dr.Soetomo, 2024)
One of preventive service is health history screening. Health history screening for BPJS Kesehatan patients can be done at primary health care and independently with smartphone. The implementation of health history screening for patients in the Puskesmas Sedati working area is still not optimal. The health history is important, so at the time of health service with medical professional, they no longer need to ask about the patient's health history. The purpose of this community development is to increase awareness in patients about the importance of health history screening and the achievement of completing BPJS Kesehatan health history screening at the Puskesmas Sedati. This method of community development includes the preparation, implementation and evaluation. The results obtained are that there are still some patients who do not understand the importance of health history screening. It provided by BPJS Kesehatan can be done independently by patients, but there are still patients who do not know how to use it, so they need assistance in filling out. The benefit of health history screening is for early detection of the risk of diseases, not to lead to the diagnosis of the diseases. The community development activities need to be carried out continuously, so the screening can continue to be carried out every year independently